2012
DOI: 10.1177/1545968312469838
|View full text |Cite
|
Sign up to set email alerts
|

Video Feedback on Functional Task Performance Improves Self-awareness After Traumatic Brain Injury

Abstract: The results suggest that the video plus verbal feedback approach used in this study was effective in improving self-awareness in people with TBI. The results also provide evidence that improvement in self-awareness was not accompanied by deterioration in emotional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 22 publications
3
87
0
Order By: Relevance
“…A recent well-conducted trial required TBI patients to learn how to prepare a meal while their competence was measured. The study compared three conditions: VSO combined with simple verbal feedback, verbal feedback alone and experiential feedback (Schmidt et al, 2012). The authors found that participants made on average 70.7% fewer mistakes following the condition with VSO versus the other conditions (approximately 20-40% reductions) which they interpret as evidence of improved "online awareness".…”
Section: Clinical Applicationsmentioning
confidence: 91%
“…A recent well-conducted trial required TBI patients to learn how to prepare a meal while their competence was measured. The study compared three conditions: VSO combined with simple verbal feedback, verbal feedback alone and experiential feedback (Schmidt et al, 2012). The authors found that participants made on average 70.7% fewer mistakes following the condition with VSO versus the other conditions (approximately 20-40% reductions) which they interpret as evidence of improved "online awareness".…”
Section: Clinical Applicationsmentioning
confidence: 91%
“…Positive discrepancy scores (participant minus relative ratings) indicate impaired self-awareness. The AQ has sound psychometric properties [35] and has demonstrated sensitivity to change in the context of awareness interventions [18]. …”
Section: Methodsmentioning
confidence: 99%
“…In contrast, a third participant who received behavioral practice with errors corrected by the therapist showed a non-significant change in errors, and instead displayed greater reliance on the therapist over time to check and correct his actions during meal preparation [16]. In a recent RCT [18], we found that multimodal feedback (that is, audiovisual plus verbal feedback on task performance) was more effective for improving error self-regulation and awareness of deficits than verbal feedback or experiential feedback alone.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have shown promising results with incorporating video feedback in other patient populations, such as brain injury [16][17], research on the use of video feedback during rehabilitation for the SCI population is limited. Our study examined the effectiveness of using immediate video feedback (IVF) in a rehabilitation setting to train manual wheelchair users with SCI in learning three wheelchair skills: (1) propelling the wheelchair on an inclined surface, (2) stationary wheelies, and (3) ascending/ descending a curb.…”
Section: Introductionmentioning
confidence: 99%